Pharmacokinetic parameters and weight change in HIV patients newly switched to dolutegravir‐based regimens in SIMPL'HIV clinical trial. Issue 11 (12th April 2021) - Courlet, Perrine; Barbieux, Charlotte; Sculier, Delphine; Wandeler, Gilles; Stoeckle, Marcel; Bernasconi, Enos; Braun, Dominique; Vernazza, Pietro; Cavassini, Matthias; Marinosci, Annalisa; Smit, Mikaela; Günthard, Huldrych F.; et al.
Abstract : This study aims to evaluate the association between dolutegravir (DTG) pharmacokinetic parameters and weight changes in treatment‐experienced people with HIV (PWHIV) from the Simpl'HIV study newly switched to a dual DTG‐based regimen. We used multivariable linear regressions to evaluate the association between DTG pharmacokinetic parameters at week 48 (derived using an established model) and weight change between week 0 and week 48. We adjusted our model for potential confounders including CD4 nadir, female sex, African origin, age, weight at week 0 and presence of a non‐nucleoside reverse transcriptase inhibitor‐based regimen before switch to DTG. The analysis included data from 39 PWHIV. An average significant weight gain of 2.4 kg was observed between baseline and week 48. DTG plasma exposure was not significantly associated with weight gain, even after adjusting for potential confounders ( P = .9). We found no significant association between DTG pharmacokinetic parameters and weight gain amongst PWHIV newly switched to a DTG‐based dual regimen.